Persepsi Guru di Gugus Langke Rembong Terhadap Implementasi Kurikulum Merdeka di Sekolah Dasar - Stefanus Divan; Gervasius Adam (Jurnal Elementaria Edukasia, 2023)
Tenquiry is intended to describe the perception of teachers in the Langke Rembong cluster regarding the implementation of the Merdeka Curriculum in primary schools. This enquiry employs a descriptive qualitative approach. The research subjects consist of 43 teachers in the Langke Rembong cluster who teach in Grade 1 and Grade 4. Data collection instruments used questionnaires distributed with the assistance of Google Forms. Data analysis techniques used data reduction, data presentation, and conclusions. The fallout of this enquiry pointed out that the implementation of the Merdeka Curriculum in the Langke Rembong cluster encountered several challenges. These challenges include ineffective training time utilization, not all teachers participating in training despite being assigned to teach in Grade 1 and Grade 4, inadequate teacher and student textbooks, difficulty in simplifying Lesson Plans (RPP), student difficulties in understanding the teaching materials, teaching materials not aligning with the students' culture in Manggarai, and ineffective evaluation practices. However, the consistent implementation of the Merdeka Curriculum has contributed to the development of students' character, and teachers agree to replace the National Standardized Examination (USBN) with portfolio assessments. Additionally, the principles of Merdeka Curriculum have been internalized into the subject matter at the primary school level. Grounded in the findings of this enquiry, it can be concluded that the implementation of the Merdeka Curriculum in the Langke Rembong cluster, from preparation to execution and evaluation, should be carried out effectively to avoid burdening both teachers and students in the learning process.